Disaster preparedness: learning from previous flood incident for future intervention/ Fatin Nur Zulkipli, Saiful Farik Mat Yatin and Nurussobah Hussin - Zulkipli, Fatin Nur; Mat Yatin, Saiful Farik; Hussin, Nurussobah (Faculty of Information Management, 2021)
Monsoon season in Malaysia give a big impact essentially related with natural disaster such floods as a common incident that happen almost every year. There is a need for intervention, for better understanding of the disaster preparedness in records management. Thus, a systematic planning is needed to plan and carry out its function and roles. The purpose of this study is to examine the coordination, organizational response and mitigation of previous floods for future intervention at one (1) of the public universities in East Malaysia. The goal of this study is also to examine disaster preparedness on paper-based data which is records and document during a flood incident and what can be learnt from a previous occurrence and come up with a range of provisions. This study used qualitative approach that involved structured interview and unstructured information. Population groups have been selected according to their role and qualification to ensure all data is credible and accurate. Finding showed that disaster preparedness on records management has not been prepared accordingly. Awareness is the main factors that contribute to the success of records disaster preparedness plan. However, emergency management in this university only focus on human safety and expensive equipment without notice about vital records.